PELATIHAN PENGOLAHAN DATA EPIDEMIOLOGI BAGI PETUGAS SURVEILAS PENYAKIT MENULAR DI KABUPATEN BANYUMAS - Dwi Sarwani Sri Rejeki; Kuswanto Kuswanto; Sri Nurlaela (Kesmas Indonesia, 2014)
ABSTRACT Most of Surveillance staffs were juggle for their jobs in Public Health Center (Puskesmas) on the area of Banyumas regency. However, it is the role of surveillance staffs in analyzing the data that will be used in Public Health Center or ministry of health. Regarding to the variety of education background to the Surveillance staffs in Banyumas, it effects to the different skill in analyzing the data in contagious diseases. Analyzing the data is very crucial area to be mastered by the surveillance staff since it will yield the information for taking the decision. The aim of this research was to improve the skill of surveillance staffs in analyzing and presenting the data in Public Health Center Distric Banyumas. The researcher conducted the training in a day at July 4th, 2013 in Biostatistics Laboratory, Public Health Department. 34 participants were joined in this training. Based on the training, there was an improvement 4.92% of knowledge and 136% skill in analyzing the data. Then it is suggested to the participant to implement the knowledge and skill that they obtained in the training, so it can yield accurate information and policy. Keywords: training, surveillance, staffs. Kesmasindo, Volume 6, (3) Januari 2014, Hal. 223-231